MEASURES AIMED AT REDUCING THE PERINATAL RISK OF PREMATURE BIRTH - Yunusova Aziza Rakhmatilloyevna (Journal of Science in Medicine and Life, 2024)
This concept in medicine of risk groups during pregnancy is necessary to minimize the possibility of developing complications that can lead to premature birth and congenital pathologies during pregnancy. Sometimes mothers-to-be who are at risk need to be admitted to a day hospital, so that doctors can monitor them for 6-8 hours a day, provide the necessary medical care and perform some procedures. Only on the basis of information provided by the attending gynecologist, a woman can be assigned to stay in the clinic during the day.